Decoding electroacupuncture’s efficacy: a comparative study on gut microbiota and metabolic profiles in C57 and 3xTg-AD mice - Deng, Chuyu; Cao, Xingyu; Wang, Xueying; Tang, Chunzhi; He, Zhenhua (Frontiers in Microbiology, 2026)
ObjectiveThis study aimed to investigate the impact of electroacupuncture (EA) on blood glucose, lipid profiles, and gut microbiota in WT (C57BL/6J) and 3xTg-AD mice with type 2 diabetes mellitus (T2DM) by examining fecal microbiota.MethodsC57BL/6J and 3xTg-AD mice were randomly divided into six groups (n = 12 per group) using a random number table: normal diet (C57-ND, 3X-ND), high-fat diet (C57-HFD, 3X-HFD), and high-fat diet with electroacupuncture (C57-EA, 3X-EA). Mice were fed either a high-fat or standard diet for 16 weeks, followed by electroacupuncture treatment at the ST36 acupoint. Following the intervention, body weight, fasting blood glucose (FBG), glucose tolerance test (GTT), and serum lipid levels were tracked. The analysis of fecal microbial communities was conducted through 16S rDNA sequencing.ResultsEA treatment significantly reduced body weight gain in C57 T2DM mice, but not in 3xTg-AD T2DM mice. It decreased the area under the curve (AUC) of the glucose tolerance test (GTT) after 16 weeks and improved lipid profiles by reducing total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C), while increasing high-density lipoprotein cholesterol (HDL-C) in both mouse models. Overall, EA demonstrated a more pronounced therapeutic effect in C57 mice compared to 3xTg-AD mice. In both types of mice, the EA group had a higher ASV abundance compared to the HFD group. EA improved α-diversity and β-diversity, and the therapeutic efficacy were impaired in 3xTg-AD mice. Microbial diversity, richness, and composition varied between 3xTg-AD and C57 mice. In 3xTg-AD mice, there was an increase in the relative abundance of Deferribacterota (phylum) and Campylobacter (class), while Proteobacteria (phylum), Bacilli (class), Oscillospira, and Rikenellaceae (family) showed a decrease. The composition changes induced by a high-fat diet (HFD) differed between 3xTg-AD and C57 mice. Electroacupuncture (EA) treatment significantly increased the Ruminococcaceae family in C57 mice and the Monoglobaceae family in 3xTg-AD mice.ConclusionEA significantly enhanced glucose metabolism and lipidemia in HFD C57 mice, but its therapeutic impact was reduced in 3xTg-AD mice. The variation in gut microbiota regulation in 3xTg-AD mice could account for the response to EA treatment.